(untitled) (UCC Student Medical Journal, 2026)
Given the cultural influences and perceptions surrounding psychiatry, this has led to hesitancy and delays in seeking mental health services and treatment. Even the process of being diagnosed is affected by cultural perceptions and physician bias, as symptomatology differs between various minority groups, resulting in misdiagnoses and further delays. Compounded with pre-existing disparities and a perception that mental health conditions are inferior to other medical conditions, cultural minorities have experienced poorer health outcomes and a reduction in quality of life. Only with a better understanding of the cultural impacts on pre- and post-diagnosis and treatment can psychiatry better serve its patients and provide effective care.